2020
DOI: 10.22541/au.158981181.19035548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into the Mechanisms of action of Chloroquine and Hydroxychloroquine and its use in COVID-19 for chemoprophylaxis

Abstract: The global outbreak of Coronavirus disease 2019 (COVID-19), caused by the Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2/2019-nCoV) has put forth a serious threat to the international public health and has ruined the global economy. Till date, no drugs have been approved for Coronavirus Disease-2019 (COVID-19), although use of some drugs in trial phase has been attempted. The drugs being used for management of COVID-19 disease include chloroquine (CQ), hydroxychloroquine (HCQ), and remdesivir. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Simultaneously, endosomal trafficking and Golgi complex organization get affected. Once the pH of lysosomes and endosomes is increased it leads to dysregulation of virus fusion with host cell and prevents further virus replication [28]. On the other hand, the neutralization of pH in endosomes and lysosomes results in obstruction in the effects of proteases which affects S protein cleavage and entry of the virus into the host cell.…”
Section: Mechanism Of Action Of Hydroxychloroquinementioning
confidence: 99%
“…Simultaneously, endosomal trafficking and Golgi complex organization get affected. Once the pH of lysosomes and endosomes is increased it leads to dysregulation of virus fusion with host cell and prevents further virus replication [28]. On the other hand, the neutralization of pH in endosomes and lysosomes results in obstruction in the effects of proteases which affects S protein cleavage and entry of the virus into the host cell.…”
Section: Mechanism Of Action Of Hydroxychloroquinementioning
confidence: 99%
“…They were used as an emergency treatment for COVID-19 patients in USA, Japan and other countries (9) . Chloroquine (CQ) and Hydroxychloroquine (HCQ) are antimalarial drugs that have been proposed to be effective against COVID-19 (10) . Later, results from systematic review and meta-analysis studies on the two drugs indicated their low efficacy in reducing mortality or lowering the risk of hospitalization in outpatients (11) .…”
Section: Introductionmentioning
confidence: 99%